IMPLEMENTATION OF IMPORTED THRIFTING POLICY IN BENGKULU CITY - Nurfya Febriza; Nour Farozi Agus; Adityo Pratikno Ramadhan (Jurnal Media Akademik (JMA), 2025)
This study aims to analyze the implementation of the import ban policy on second-hand clothing (imported thrifting) in Bengkulu City and to reveal the gap between central government regulations and actual conditions in the field. The phenomenon of imported thrifting continues to flourish despite the official ban through Minister of Trade Regulation No. 40 of 2022. This research adopts a qualitative approach, utilizing in-depth interviews, observations, and document analysis. Informants include traders, consumers, and representatives from the Bengkulu City Department of Industry and Trade. The findings indicate that the implementation of the imported thrifting policy in Bengkulu faces significant challenges, including the lack of local institutional involvement in policy formulation, the limited authority of the Department of Industry and Trade in law enforcement, resistance from business actors and consumers who depend on thrifting as an economic alternative, and the influence of geographical, socio-economic, and political conditions. This study concludes that there is a significant implementation gap between national regulations and local practices. A more adaptive, locally participatory, and institutionally strengthened policy is required to ensure the effective realization of the policy’s objectives.